Sketch of King Williams Land by the Innuit In-nook-poo-zhu-jook in 1869 - Hall, Charles Francis, 1821-1871 (United States. Navy Department;, 1869)
"Narrative of Capt. Hall's 2d Arctic expediton, 1879." Grayscale;